Potential use of the hemagglutinin-neuraminidase glycoprotein of newcastle disease virus expressed in Rachiplusia nu larvae as anImmunogen for chickens - Chimeno Zoth, Silvina Andrea (2009)
The hemagglutinin-neuraminidase glycoprotein of Newcastle disease virus (NDV) was obtained as a recombinant antigen in Rachiplusia nu larvae. When it was used as an immunogen in chickens, a solid immune response, including neutralizing antibodies, was detected, demonstrating the potential use of this simple and economic strategy in the design of recombinant anti-NDV vaccines.